Comparative Evaluation of Frictional Resistance Between Conventional, Self-Ligating, and Ceramic Brackets Using Different Archwire Materials: An In Vitro Study (Bangladesh Journal of Medical Science, 2026)
Background Frictional resistance at the bracket-archwire interface is a critical determinant of force delivery during sliding mechanics. Bracket design, slot material, ligation method, and archwire alloy may modify static and kinetic friction, thereby influencing clinical efficiency during alignment and space closure. Methods This in vitro experimental study compared frictional resistance among three 0.022-inch slot bracket systems: conventional stainless steel brackets with elastomeric ligation, passive selfligating stainless steel brackets, and polycrystalline ceramic brackets with elastomeric ligation. Three archwire materials were tested: 0.019 x 0.025-inch stainless steel, nickel-titanium, and beta-titanium. Ninety bracket-archwire assemblies were prepared, with 10 specimens per bracket-wire combination. Testing was performed using a universal testing machine at a crosshead speed of 5 mm/min under artificial saliva lubrication at 37 degrees C. Static frictional resistance and kinetic frictional resistance were recorded in Newtons. Data were analysed using two-way ANOVA and Tukey post hoc tests. Results Mean static friction differed significantly by bracket type and wire material (p